Evaluation of non-vital teeth with various endodontic pathologies-a retrospective study - PRASHAANTHI. N,; NASIM, IFFAT; SHANTHA SUNDARI .K.K, (The journal of contemporary issues in business and government, 2020)
Most of the time non-vital teeth are associated with various pathologies. The early intervention would save the teeth from its loss. Depending on the etiology and the duration, the pathology differs among the non-vital teeth. The aim of this study was to evaluate non-vital teeth with various endodontic pathologies. This retrospective study included patients who were diagnosed with non-vital teeth from July 2019 to March 2020 in a dental hospital. The case records of all patients were retrieved which included the clinical , radiographic examination and treatment done for the patients. Variables such as age, gender, any associated endodontic pathologies were retrieved from the case sheets. Data was tabulated and was subjected to statistical package IBM SPSS version 20.0.Around 80,000 patients were reviewed and 238 patients met the inclusion criteria.Out of 238 patients, 71.8% were males and 28.2% were females.On analysing the prevalence of non vital teeth among different age groups, 21-30 years age group (32.8%) were more affected. On comparing the non vital teeth with endodontic pathology ,non-vital teeth without periapical lesion (74.4%) were found to be in a higher prevalence. Among non-vital teeth with endodontic pathology, periapical abscess (14.3%) was found to have higher prevalence followed by periapical cyst (2.9%) and calcified canal (2.9%).On analysing the prevalence of non vital teeth among gender , males (71.8%) were more affected. No statistically significant association was found between age, gender and non vital teeth. (p>0.05).Within the limitation of the study, the prevalence of non-vital teeth without periapical lesion were found to be higher. Among non-vital teeth with endodontic pathology, the most common pathology was chronic periapical abscess.Males were more affected with non vital teeth and had higher prevalence among the 21-30 years age group.